Anti-tumour effect of low molecular weight heparin in localised lung cancer: a phase III clinical trial. Issue 4 (4th October 2018) - Meyer, Guy; Besse, Benjamin; Doubre, Hélène; Charles-Nelson, Anaïs; Aquilanti, Sandro; Izadifar, Armine; Azarian, Reza; Monnet, Isabelle; Lamour, Corinne; Descourt, Renaud; Oliviero, Gérard; Taillade, Laurent; et al.
The anti-tumour and anti-metastatic properties of heparins have not been tested in patients with early stage cancer. Whether adjuvant low molecular weight heparin (LMWH) tinzaparin impacts the survival of patients with resected non-small cell lung cancer (NSCLC) was investigated. Patients with completely resected stage I, II or IIIA NSCLC were randomly allocated to receive subcutaneous tinzaparin 100 IU·kg −1 once a day for 12 weeks or no treatment in addition to standard of care. The trial was open-label with blinded central adjudication of study outcomes. The primary outcome was overall survival. In 549 patients randomised to tinzaparin (n=269) or control (n=280), mean±sd age was 61.6±8.9 years, 190 (34.6%) patients had stage II−III disease, and 220 (40.1%) patients received adjuvant chemotherapy. Median follow-up was 5.7 years. There was no significant difference in overall survival between groups (hazard ratio (HR) 1.24, 95% CI 0.92–1.68; p=0.17). There was no difference in the cumulative incidence of recurrence between groups (subdistribution HR 0.94, 95% CI 0.68–1.30; p=0.70). Adjuvant tinzaparin had no detectable impact on overall and recurrence-free survival of patients with completely resected stage I−IIIA NSCLC. These results do not support further clinical evaluation of LMWHs as anti-tumour agents. Whether the antimetastatic properties of heparins benefit patients with early-stage cancer is unknown. In this phase III trial, adjuvant tinzaparin in patients with resected lung cancer had no impact on overall survival and tumour recurrence. http://ow.ly/RZt030lpCuQ